Autophagy Modulation by Viral Infections Influences Tumor Development - Leonardi, Lucas; Sibéril, Sophie; Alifano, Marco; Cremer, Isabelle; Joubert, Pierre-Emmanuel (Frontiers in Oncology, 2021)
Autophagy is a self-degradative process important for balancing cellular homeostasis at critical times in development and/or in response to nutrient stress. This is particularly relevant in tumor model in which autophagy has been demonstrated to have an important impact on tumor behavior. In one hand, autophagy limits tumor transformation of pre-cancerous cells in early stage, and in the other hand, it favors the survival, proliferation, metastasis and resistance to anti-tumor therapies in more advanced tumor. This catabolic machinery can be induced by an important variety of extra and intracellular stimuli. For instance, viral infection has often been associated to autophagic modulation and the role of autophagy in virus replication differs according to the virus studied. In the context of tumor development, virus-modulated autophagy can have an important impact on tumor cells fate. Extensive analyses have shed light on the molecular and/or functional complex mechanisms by which virus-modulated autophagy influence pre-cancerous or tumor cell development. This review includes an overview of discoveries describing the impact of an autophagy perturbation during viral infections on tumor behavior.